The effect of ownership-control divergence on investment sensitivity to idiosyncratic risk: evidence from an emerging economy - Caixe, Daniel Ferreira (2018)
This study investigates the moderating role of the agency conflict between controlling and minority shareholders on the investment-risk relationship. When the ownership-control structure is concentrated, the agency theory indicates that the separation between cash-flow rights and voting rights induces the controlling shareholder to extract private benefits. To assess the effect of ownership-control divergence on the investment-risk relation, we use system generalized method of moments estimator (SYS-GMM) in longitudinal data from 412 Brazilian firms between 1997 and 2010. Our results show that investment is less sensitive to idiosyncratic risk for companies in which the largest shareholder presents high levels of ownership-control divergence. The impact of excess voting rights on the investment-risk sensitivity holds after we group firms according to distinct corporate governance and financial characteristics, such as financial constraints, family control, board independence, and the type of control-enhancing mechanism. Board independence does not affect controlling shareholders\' behavior toward risky investments. Among the control-enhancing mechanisms, the issuance of dual class shares is the main driver of the lower investment sensitivity to idiosyncratic risk. Our findings are consistent with entrenchment effects in the sense that dominant shareholders may select riskier projects when investing other people\'s money, which have both managerial and policy implications.